The Symbolic-Compliance Gap and Public Perceptions of Sharia Law Enforcement in Aceh, Indonesia: Insights from Becak Drivers - Maskur; Irman; Lukmanul Hakim (Journal of Asian Social Science Research, 2024)
This study explores the perceptions of becak (three-wheeled motorcycle taxis) drivers in Aceh regarding the implementation and enforcement of Sharia law, offering insights into the interplay between religious governance and its influence on social order, morality, and justice. Drawing on in-depth interviews with 30 drivers from diverse socioeconomic backgrounds, the research reveals a complex relationship between the symbolic authority of Sharia law and community compliance. While many participants view the law as a representation of public discipline and Aceh's religious heritage, they frequently critique it as being largely symbolic and ineffective in fostering genuine moral transformation. Thematic analysis identifies key concerns, including superficial compliance, inconsistent enforcement, and perceived injustices, which collectively undermine public confidence in the law. To address these challenges, the study introduces the theory of Symbolic- Compliance Dynamics, which highlights the disjunction between external adherence to regulations and internal moral commitment. The findings suggest that a community-centered approach emphasizing fairness, consistent application, and meaningful moral education is essential for achieving more substantive outcomes. While these results are specific to Aceh, they provide a foundation for further research on the societal impacts of Sharia law in other regions and contexts.